From Passive to Interactive: The Impact of Blooket Gamification to Enhance Students' Learning Motivation in Islamic Religious Education - Ahmad Abdul Hamid; Ismail Ismail; Suja’i Suja’i; M. Agung Hidayatullah; Zarkasi Zarkasi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The decline in student engagement and motivation in Islamic Religious Education (PAI) remains a significant challenge, particularly in pesantren environments where traditional teaching methods are dominant and personal gadgets are strictly prohibited. This study aims to analyze the implementation of Blooket gamification using a classical (single-screen) model as an innovative pedagogical strategy to increase students' enthusiasm for PAI learning at MA Al Wathoniyyah Semarang. Using a qualitative approach with a descriptive case study design, data were collected through intensive participant observation, in-depth interviews, and documentation from PAI teachers and 10th-grade students, then analyzed using the Miles and Huberman interactive model. The results indicate that projecting Blooket onto a main screen successfully transformed classroom dynamics from passive to highly interactive. This approach fostered a unique